Elevated procalcitonin is associated with bacterial infection during acute liver failure only when unrelated to acetaminophen intoxication. Issue 7 (July 2017) - Mallet, Maxime; Haq, Maela; Tripon, Simona; Bernard, Maguy; Benosman, Hedi; Thabut, Dominique; Rudler, Marika
Abstract : Aim: The aim of this study was to evaluate the accuracy of procalcitonin (PCT) in predicting bacterial infection and survival without transplantation upon admission in the ICU for acute liver failure (ALF). Patients and methods: From January 2009 until October 2015, all cases of ALF patients admitted in our ICU were retrospectively reviewed and included in the study if the PCT level upon admission was available. Patients with pre-existing liver pathology or ALF in a context of already advanced multiorgan failure were excluded. The main clinical and biological characteristics of patients were recorded, as well as the etiology of ALF, diagnosis of bacterial infection (bacteriologically documented or suspected), and outcome. Results: 35 patients were included: 46% men, mean age 42 years, initial prothrombin ratio 31%, PCT 9.8 mg/l (0.7–49), and PCT more than 2 mg/l in 54% of cases. Etiology was acetaminophen intoxication in 18/35 (51%) cases. Sepsis was diagnosed in 9/35 (26%) cases, most frequently pneumonia with 4/9 cases. Survival without liver transplantation (LT) was observed in 28 (80%) cases. The median PCT was not different in patients with or without bacterial infection [6.3 mg/l (0.6–16) vs. 1.2 mg/l (0.8–9.7), P =0.8]. The median PCT was not different in patients who survived without LT [7.1 mg/l (0.9–16.1) vs. 0.75 mg/l (7.7–11.5), P =0.06]. In patients with ALF unrelated to acetaminophen intoxication, the median PCT was higher in patients with bacterial infection [1.1 mg/l (0.9–4) vs. 0.5 mg/l (0.3–0.8), P =0.01], but was similar in patients who did not survive without LT [0.7 mg/l (0.4–1.1) vs. 0.8 mg/l (0.4–2.2), P =0.6]. In the overall cohort, the median C-reactive protein (CRP) and leukocyte count were higher in patients who developed bacterial infection [40 mg/l (19–60) vs. 16 mg/l (6–34), P =0.04; 11.9 G/l (8.3–19) vs. 7.9 G/l (6–12.6), P =0.05]. The median CRP and leukocyte count were not significantly different in survivors versus nonsurvivors without LT. Conclusion: PCT was an accurate predictor for the diagnosis of bacterial infection only in patients with ALF unrelated to acetaminophen intoxication. CRP was higher in patients who developed infection and could also be an interesting tool in ALF patients.